Meeting the expectations of our Caribbean people - Patterson, P. J. (Jamaica Information Service KingstonJM, 2003)
Reports on matters that were the focus of deliberations at the 24th Meeting of the Conference of Heads of Government. Highlights matters such as regional governance, progress in the establishment of the CSME, external relations, trade negotiations and bilateral exchanges.